Evaluation of a Family-Based Intervention Program for Children of Mentally Ill Parents: Study Protocol for a Randomized Controlled Multicenter Trial - Wiegand-Grefe, Silke; Filter, Bonnie; Busmann, Mareike; Kilian, Reinhold; Kronmüller, Klaus-Thomas; Lambert, Martin; Norra, Christine; von Klitzing, Kai; Albermann, Kurt; Winter, Sibylle Maria; Daubmann, Anne; Wegscheider, Karl; et al. (Frontiers in Psychiatry, 2021)
Background: Children of mentally ill parents have a three to seven times higher risk to develop mental disorders compared to the general population. Specialized prevention and intervention programs for this high risk group have been developed, but their evaluation under high methodological standards has been insufficient to date. Moreover, effectiveness and the cost-effectiveness data of the respective programs until today is very scarce and at the same time constitutes the precondition for the programms´ implementation into regular health care. Methods: The study is a two-group randomized controlled multicenter trial conducted at seven study sites throughout Germany and Switzerland. Participants are families with mentally ill parents and their children aged from 3 to 19 years. The intervention comprises six to eight semi-structured sessions over a period of roughly six months. Topics discussed in the intervention include, for example, the parent’s mental illness, coping, family relations and social support. Families in the control condition will receive treatment as usual. The children’s mental health, assessed using the K-SADS-PL by blinded external raters will constitute the primary efficacy outcome. Further outcomes will be assessed from the parent’s as well as from the children’s perspective. Participants are investigated at baseline, 6, 12 and 18 months. In addition to the assessment of various psychosocial outcomes, a comprehensive health-economic evaluation will be performed. Discussion: This paper describes the implementation and evaluation of a family-based intervention program for children of mentally ill parents (CHIMPs) in the regular health care system in Germany and Switzerland. A methodologically challenging study design is used to reflect the complexity of the actual health care situation. This trial will contribute to the regular health care for the high-risk group of children of mentally ill parents. Clinical Trial Registration: www.ClinicalTrials.gov, identifier NCT02308462; German Clinical Trials Register: DRKS00006806